Analysis Of The Potential Of Roadside Parking As A Source Of Regional Original Revenue (PAD) In Surabaya City - Pradana Affan Abdillah; Andi Patriadi; Sajiyo Sajiyo (Syntax Corporation Indonesia, 2025)
The ever-increasing demand for parking facilities in urban areas highlights the importance of parking system management to support Local Own Revenue (PAD). This study explores the potential of roadside parking in Surabaya City as a significant contributor to PAD, emphasizing the relationship between effective parking management and urban mobility challenges. Data were collected through field surveys at various roadside parking spots, revenue potential calculations, and an analysis of factors influencing parking efficiency, including both supporting and inhibiting elements. The findings indicate that optimizing parking policies, implementing fair and competitive parking levy rates, and improving parking infrastructure can significantly enhance PAD contributions. Moreover, the results underscore the role of technology, such as electronic parking systems, in reducing revenue leakage and improving transparency. This study also identifies key factors that hinder the realization of optimal revenue potential, such as illegal parking, limited parking capacity in high-demand areas, and insufficient public awareness about parking regulations. Addressing these issues through stricter law enforcement, enhanced public education, and better integration of parking facilities with public transportation systems can lead to a more efficient transportation ecosystem. The study concludes that effective roadside parking management not only supports local revenue generation but also helps mitigate traffic congestion and fosters economic development by ensuring smoother urban mobility. By addressing both supporting and inhibiting factors, the Surabaya City government has an opportunity to transform roadside parking into a sustainable and substantial revenue source while improving the overall quality of urban life.